Terapi Komplementer Acupressure untuk Menurunkan Dyspnea Pasien dengan Efusi Pleura - Ramal Saputra; Agung Waluyo (FORIKES, 2022)
The most common symptom in patients with pleural effusion is dyspnea. In addition to pharmacological therapy, acupressure therapy is one of the complementary non-pharmacological treatments in the form of physiotherapy with massage and stimulation of special points on the body. Currently, not much is known about the benefits of acupressure for health. The aim of acupressure is to provide significant benefits, especially in reducing shortness of breath in patients with pleural effusion. This case study was conducted in one of the treatment rooms at the RSUD in Lampung Province. The degree of dyspnea was assessed by the Brog Dyspnea Scale. Cases were patients with the main complaint of shortness of breath, accompanied by cough, chest pain, decreased appetite, nausea and vomiting since 1 week before admission to the hospital. The results of physical examination and investigations showed pleural effusion ec CHF. During hospitalization, acupressure was given to patients who had dyspnea and decreased oxygen saturation for 7 days. The results of this therapy showed a decrease in the Brog's dyspnea scale in these patients. This therapy can be done by the patient independently or with the help of a nurse, and there are very few side effects. In conclusion, acupressure is a complementary therapy that is easy to do, minimal side effects and can be used in patients with respiratory disorders.Keywords: acupressure; pleural effusion; Brog's dyspnea scaleABSTRAK Gejala yang paling sering timbul pada pasien efusi pleura adalah dyspnea. Selain terapi farmakologis, terapi acupressure merupakan salah satu pengobatan non farmakologis komplementer berupa fisioterapi dengan pemijatan dan stimulasi terhadap titik-titik khusus pada tubuh. Saat ini belum banyak diketahui manfaat acupressure untuk kesehatan. Tujuan acupressure adalah memberikan manfaat yang signifikan, terutama dalam menurunkan sesak nafas pada pasien dengan efusi pleura. Studi kasus ini dilakukan di salah satu ruang perawatan di RSUD di Provinsi Lampung. Tingkat dyspnea dinilai dengan Brog Scale dyspnea. Kasus adalah pasien dengan keluhan utama sesak nafas, disertai batuk, nyeri dada, nafsu makan berkurang, mual dan muntah sejak 1 minggu sebelum masuk kerumah sakit. Hasil pemeriksaan fisik dan pemeriksan penunjang menunjukkan efusi pleura ec CHF. Selama dirawat telah diberikan acupressure terhadap pasien yang mengalami dyspnea dan penurunan saturasi oksigen selama 7 hari. Hasil terapi ini menunjukkan penurunan skala dyspnea Brog pada pasien tersebut. Terapi ini dapat dilakukan oleh pasien secara mandiri ataupun dengan bantuan perawat, serta sangat minim akan efek samping. Sebagai kesimpulan, acupressure merupakan terapi komplementer yang mudah dilakukan, minim akan efek samping dan dapat digunakan pada pasien dengan gangguan pernafasan.Kata kunci: acupressure; efusi pleura; skala dyspnea Brog